Sin city treachery eaudiobook - Gerlacher, Gary (AJ Docker Medical Thriller, 2024)
Las Vegas, the entertainment capital of the world, hosts an F1 race, the largest sporting event in the city's history and a prime target for terrorism. With over a half million people descending on the Strip for the event, a bomb detonated in a parking garage days before the race. In the emergency room, Doc fights to save the lives of a pregnant doctor and her premature baby injured in the blast, spurring him to risk his own life to find justice for the victims. He is joined by his girlfriend Lana, a smart, ambitious reporter, his friend and colleague, Rick, and his trained ex-police dog Banshee. Their investigation takes them from a seedy bar to iconic landmarks around Las Vegas and crescendos on the night of the race when chaos reigns in the city. As the sun rises, they reveal a deceptive scheme to close the case. An action-packed thriller, Sin City Treachery entertains with a story that leaves listeners guessing until the end.